The New Approaches to Improve the Morpho-Functional Readiness for Systematic School Training of Six-Year Old Children with Iron Deficiency - S.A. Mokiia-Serbinа; V.V. Chechel (Zaslavsky O.Yu., 2016)
Objective: to increase morpho-functional readiness for systematic school training of six-year old children with iron deficiency. Materials and methods. The study included 155 six-year old children in preschools with diagnosed iron deficiency and 50 healthy children. Patients were randomized into the basic group (52 children with established latent iron deficiency and 25 persons with iron deficiency anemia I degree) and comparison group (53 children with latent iron deficiency and 25 children with iron deficiency anemia I degree). Children with iron deficiency received standard iron therapy. In the basic group combined drug with multicomponent action was additionally used. There were studied such parameters as anthropometric (height, weight, chest perimeter), fine motor skills of hands, biological (change of first teeth, the ratio of the circumference of the head to the body length, the degree of ossification of the left hand skeleton). Results. Under the combined therapy anthropometric parameters and fine motor hand skills restored to the level of healthy children reliably faster. Parameters ofbiological development improved in both groups with no statistical difference. Conclusions. Iron therapy supplied by multi-component drug in six-year old children with iron deficiency enhances their morpho-functional readiness for systematic school training.